Interaction effects in the prediction of university drop-out for psychology students - Rodrigo, María F.; Molina, J. Gabriel; García Ros, Rafael; Pérez González, Francisco (Anales de Psicología / Annals of Psychology, 2012)
Although there have been a number of studies which have analysed university dropout, there is little information on the incidence and determinants of this phenomenon in the degree of Psychology. In this study, we analyze the capacity of a set of socio-demographic and educational variables to predict university dropout. The data came from the students admitted to this degree at the University of Valencia in 2000 and 2001 (N = 785). The analysis was based on the comparison of nested logistic regression models in which the starting model included first-order interaction effects of the variables under consideration. Compared to previous studies in this area, the most innovative result in the prediction of university dropout is the moderator effect of the high school curriculum on both the students high school average, and on the order of preference stated in the university enrolment. These results allow us to raise some hypotheses about the consequences of assigning the degree of Psychology to the branch of Health Sciences and the subsequent change in the type of training required to gain access to this degree.